Knowledge Regarding the Administration and Regulation of High Alert Medications among Nurses in Tertiary Care Hospitals, Bannu KPK: Administration and Regulation of High Alert Medications among Nurses - Bibi, Saira; Saira, .; Ihsan, Ayesha; Nisa, Nafisa Un; Begum, Hameeda; Parveen, Nishat; Rehman, Atiq Ur; Khan, Sheraz (Pakistan Journal of Health Sciences, 2025)
High-alert medications (HAMs) have a significant potential for causing severe harm if mismanaged. Proper administration and regulation of these drugs are critical to ensuring patient safety. However, limited knowledge and adherence to safety practices among healthcare professionals increase the risk of medication errors. Objective: To assess nurses’ knowledge regarding the administration and regulation of high-alert medications. Methods: Using convenience sampling, this descriptive cross-sectional study involved 113 registered nurses from tertiary care hospitals in Bannu. Data were collected through an adopted questionnaire distributed via Google Forms, encompassing demographic details and specific questions on HAM administration and regulation safety practices. Data analysis included descriptive and inferential statistics using Microsoft Excel. Results: Among the respondents, 64.3% correctly identified HAMs as posing significant risks, yet 35.7% displayed critical knowledge gaps in identifying safe administration practices. Errors were most notable in dosage calculations, drug labeling, and administration methods, particularly for potassium chloride and epinephrine. While 57.1% acknowledged the importance of double-checking doses, only 42.9% demonstrated comprehensive knowledge of storage protocols. Significant gaps in education and training were identified, highlighting the need for improved safety practices. Conclusions: It was concluded that substantial gaps in nurses’ knowledge and practices related to HAMs, underscoring the necessity for targeted training programs. Enhanced education, adherence to safety protocols, and interdisciplinary collaboration are essential to minimizing medication errors and improving patient safety.